Konstruksi Maskulinitas pada Laki-Laki Korban Pelecehan Seksual - Nala Suhaila; Triny Srihadiati (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This study aims to examine and understand how constructions of masculinity are formed and affected in male victims of sexual abuse. In the context of a society that often defines masculinity with strength, toughness and dominance, the experience of sexual abuse can create dissonance in the masculine identity of the victims. This research uses qualitative research methods using observation, interview and literature study techniques. The results showed that social and cultural norms related to masculinity have a significant influence on the experiences of male victims of sexual abuse, especially in terms of how they feel, deal with, and obtain support for the event. These masculinity-related stigmas and stereotypes can hinder the recovery process for male victims, as they may feel that acknowledging the abuse will damage their masculine identity. In addition, the lack of understanding and empathy from society and law enforcement towards male victims can exacerbate their situation, ultimately leading to disparities in the protection and handling of sexual violence cases between male and female victims.